Influence of Sanitation on Employee Performance at National Social and Security Fund, Kenya - On'gonge , Hezra O.; Ng'eno , Weldon K. (International Journal of Health Sciences, 2022)
Purpose: Organizations exist to produce goods and services to meet the customers' demands and to give favorable working environment for workers as outlined in the Occupational Health and safety standards Act (2007). Since organizations depend on the employees as the main working force to help them meet their objectives, the provision of safe and healthy program will depend on the size of the organizations. The purpose of this study was to examine the extent to which sanitation influences employee performance at NSSF. Methodology: In the research methodology, Descriptive research design was used where 4750 staff at the National Social Security Fund (NSSF), headquarters in Nairobi, were considered as the population. Stratified and purposive samplings were used in this study where a sample of 369 from the population was considered. The study used structured questionnaires and observation methods as instruments of data collection. Descriptive statistics was used to analyse mean, percentages and Standard deviation. This was aided by using Statistical package for social sciences (SPSS) software. Qualitative data was examined using inferential statistics. The link between sanitation as an independent variable and employee performance as a dependent variable was examined using a linear regression model. Findings: Research's findings suggested that a number of illnesses and disorders were brought on by poor sanitation. The research validated the 1959 Two-Factor Theory put out by Frederick Herzberg. According to the theory, two factors"”motivators, or things that will gratify an employee, and hygiene factors, or items that are related to employees' mental health"”have an impact on how well employees perform inside an organization. Unique contribution to theory, policy and practice: This study is distinctive since it emphasizes how sanitation would help to boost performance while an unfavorable work environment would make the employees unhappy, which would lower their performance. According to the report, firms should create Sanitation policies and regulations that comply with the Occupational Safety and Health Act of 2007, as employee performance is a major factor in organizational advancement. Offices are becoming more often filthy as a result of the company's growing customer base, necessitating stronger waste control. Additional cleaners should be engaged, and restrooms should stock extra paper towels and hand soaps, among other necessities, in order to undertake cleaning more frequently.